A morphological study of the brain of Solea senegalensis. l. The telencephalon - Rodriguez-Gomez, F.J.; Sarasquete, C.; Muñoz-Cueto, J.A. (Murcia : F. Hernández, 2000)
In this paper we present an anatomical description of the telencephalon of Solea senegalensis based on cresvl violet and haematoxilin-eosin-stained serial transverse sections. This work was conducted as a basis for the ~ r e c i s elo calization of neuroendocrine - - territories in the brain of a species with growing interest in marine aquaculture. The external asymmetric morphology of Senegalese sole is correlated with the asymmetry of the forebrain. The right olfactory nerve and bulb are larger than the contralateral ones and this asyrnmetry is also extended to the cerebral hemispheres. The olfactory bulb comprises an outer olfactory nerve fiber layer, a glomerular layer, an external cellular layer, a secondary olfactory fiber layer and an interna1 cellular layer. The telencephalic hemispheres can be divided in area dorsalis and area ventralis, consisting of eleven and eight cell masses, respectively. The area dorsalis comprises five subareas: a pars medialis (Dm), subdivided into four nuclei termed Dml to Dm4; a pars dorsalis (Dd); a pars lateralis (DI), which consists of dorsal (Dld), ventral (Dlv) and posterior (Dlp) subdivisions: a pars centralis (Dc); and more caudally, a pars posterioris (Dp), which is very prominent in this species. A nucleus taenia (NT) was observed in the tiansitional region between area dorsalis and area ventralis. The area ventralis consists of pars dorsalis (Vd), pars ventralis (Vv), pars supracommissuralis (Vs), pars postcommissuralis (Vp), pars lateralis (VI), pars centralis (Vc), pars intermedia (Vi) and nucleus entopeduncularis (E). A periventricular organ, that we have termed lateral septal organ (LSO), was observed in the ventral telencephalon, media1 to VV.